Spontaneous reduction of an incarcerated gravid uterus after myomectomy in the second trimester: A case report. Issue 9 (March 2019) - Tong, Chun; Wang, Yan; Liu, Zhaohui; Zhao, Yangyu; Xu, Yan; Wang, Wei
Abstract: Rationale: During a normal pregnancy, in the 1st trimester uterus lies in pelvis and enlarges in size as the pregnancy advances. By 14 weeks of gestation, the gravid uterus transforms from a pelvis to an abdominal organ and a retroverted uterus will correct as the fundus rises out of the pelvis and falls forward to its normal anatomical position. If the uterus remains in the pelvic cavity after 14 weeks of gestation, it is referred to as an incarcerated uterus. Patient concerns: A 31-year-old gravida 3 para 0 woman was admitted to our obstetrics unit at 20 weeks' gestation with the complaint of severe persistent upper abdominal pain for over 12 hours. Diagnosis and interventions: A diagnosis of fibroid degeneration was made through ultrasound and magnetic resonance imaging. The patient was hospitalized with conservative treatment. An abdominal myomectomy was performed at 22 weeks' gestation because her condition had deteriorated. Incarcerated uterus was not suspected even at the time of myomectomy. But within 24 hours after myomectomy, diagnosis of incarcerated gravid uterus was made by ultrasound. Outcomes: Incarcerated gravid uterus was found spontaneously reduced three weeks after myomectomy by ultrasound. A transverse Cesarean incision was performed at 32 weeks' gestation. A male infant weighing 2120 g was delivered with Apgar scores of 10 and 10 at 1 and 5 minutes, respectively. Postoperative course was uneventful. Lessons: Incarceration of the gravid uterus is relatively rare and it is difficult to diagnose. This patient's findings suggested the incarceration of gravid uterus can be a transient abnormal position. The results of this study indicates that the incarcerated uterus when associated with fibroid is spontaneously reduced after removal of the fibroid.